Relationship between proxies for Type II fiber type and resting blood pressure in Division I American Football Athletes - DiCesare, Christopher A.; Adams, James R.; Claytor, Randal P.; Ward, Rose M.; Cox, Ronald H. (International Journal of Health Sciences, 2017)
Objective: The risk for cardiovascular disease is well-documented. Perhaps surprisingly, specific athletic populations, including American football players, exhibit increased risk for cardiovascular disease as presented by elevated blood pressure. There is evidence suggesting a link between muscle fiber type distribution and resting blood pressure. Acknowledging this association, it becomes important to clarify an individual’s risk for developing cardiovascular disease later in adulthood. The purpose of this study was to assess football performance measures—in particular proxies for muscular power—and their effect on resting blood pressure in football athletes. Methods: A total of 80 collegiate-level football players participated in this study. Each participant’s body fat %, body mass index, waist circumference, and mean arterial pressure (MAP) were measured. Participants performed one-repetition maximums of bench press, back squat, 40-yard dash, and vertical leap, and a power index (PI) defined as the product of vertical leap and mass. Linear regressions were run between body composition variables and performance measures for all players and a subset of skill players only. Results: The PI was found to be positively, significantly correlated with MAP in all players (r = 0.269; P = 0.035) and the skill players subset (r = 0.425; P = 0.004). Conclusion: The results of the present study indicate an association between muscle fiber type distribution, as indicated by muscular power capacity, and resting blood pressure.